Naprężenia w Rurze Cylindrycznej Obracającej się ze Zmienną Prędkością Kątową - Singh, Avtr; Puri, Pratap (Engineering Transactions, 1963)
This paper is concerned with the problem of stress distribution in an infinite circular cylinder rotating about its axis with variable angular velocity. The particular cases considered are those when w the angular velocity, is proportional to (1) cos st (2) cos2 st and (3) e-st where S is a given constant and t is the time. In cases (1) and (2) the but whereas the direction of rotation is reversed in angular velocity becomes zero first at t = 7/2s, former case, the latter preserves the same direction after the lapse of this time. This cycle is then repeated. The solution for case (2) can not be obtained from case (1) by simple superposition because of the occurance of w2 in the first equation of motion. In case (3) the angular velocity is taken to vanish exponentially with time. The stresses and dis- placements are found in all cases in closed form. As far as the author's knowledge is inertia terms in concerned the problems treated are of new equations of type where the motion are also included.